2016
DOI: 10.1038/nature17418
|View full text |Cite
|
Sign up to set email alerts
|

Northern Hemisphere hydroclimate variability over the past twelve centuries

Abstract: Accurate modelling and prediction of the local to continental-scale hydroclimate response to global warming is essential given the strong impact of hydroclimate on ecosystem functioning, crop yields, water resources, and economic security. However, uncertainty in hydroclimate projections remains large, in part due to the short length of instrumental measurements available with which to assess climate models. Here we present a spatial reconstruction of hydroclimate variability over the past twelve centuries acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
156
3
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(164 citation statements)
references
References 54 publications
3
156
3
2
Order By: Relevance
“…They argue that the medieval warming in the Arctic did not extend to Greenland, thus challenging our long-held understanding of the settlement and later abandonment of Norse Greenland. This is in direct contradiction to the spatial temperature reconstructions of Mann et al (2009) and Ljungqvist et al (2012Ljungqvist et al ( , 2016, which instead point to very warm conditions in Greenland at that time. As we will see, our results show that the Greenland sector of the Arctic indeed was warm during the 10 th and especially the early 11 th centuries CE.…”
contrasting
confidence: 43%
“…They argue that the medieval warming in the Arctic did not extend to Greenland, thus challenging our long-held understanding of the settlement and later abandonment of Norse Greenland. This is in direct contradiction to the spatial temperature reconstructions of Mann et al (2009) and Ljungqvist et al (2012Ljungqvist et al ( , 2016, which instead point to very warm conditions in Greenland at that time. As we will see, our results show that the Greenland sector of the Arctic indeed was warm during the 10 th and especially the early 11 th centuries CE.…”
contrasting
confidence: 43%
“…The central European transitional climate zone migrated over central Europe on decadal to millennial time-scales, mostly due to external forcing mechanisms (Ljungqvist et al 2016). However, the complex reconstruction teleconnections amongst the cryosphere, ocean and atmosphere are often biased by more-local influences in terrestrial records (Magny 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Rehfeld and Laepple (2016) found that the linkage between temperature and precipitation over Asia is timescale dependent, and that model simulations agree with proxy data on shorter timescales but disagree on longer timescales. these results, together with the Northern Hemispheric proxy-model comparison by Ljungqvist et al (2016), indicate that the hydroclimate responses to low-frequency temperature changes are not yet sufficiently well known.…”
mentioning
confidence: 88%